An extension of a multicenter, randomized, split‐face clinical trial evaluating the efficacy and safety of chromophore gel‐assisted blue light phototherapy for the treatment of acne - Nikolis, Andreas; Fauverghe, Stéphane; Scapagnini, Giovanni; Sotiriadis, Dimitrios; Kontochristopoulos, George; Petridis, Athanasios; Rigopoulos, Dimitrios; Dessinioti, Clio; Kalokasidis, Konstantinos; Antoniou, Christina (International journal of dermatology, 2018)
A variety of laser/light‐based devices have been reported to be effective for the treatment of acne, yet no long‐term data on efficacy and safety have been published. A first 12‐week clinical trial (“Main trial”) recently demonstrated that the KLOX BioPhotonic System, an LED blue light device using photo‐converter chromophores, can significantly improve moderate and severe facial acne vulgaris with an excellent safety profile. This Extension trial followed the Main trial, using the same BioPhotonic System, with the same dose and instructions for use, on patients having already completed treatment in the Main trial. Main objectives of this open‐label long‐term extension 12‐week study were to evaluate the efficacy of the KLOX BioPhotonic System on the untreated hemiface during the Main trial, as well as the duration of response on the hemiface treated during the first 12‐week Main trial. Despite their young age (mean age: 21.6 years) and their 12‐week participation in the Main trial, 49 (54.4%) of the total number of patients who participated in the Main trial enrolled in this additional 12‐week Extension trial. Baseline grading of acne was performed with the Investigator's Global Assessment (IGA) scale. For each patient, the hemiface randomly selected as a control during the Main trial received 6 weeks of treatment (twice weekly) and was then followed up for an additional 6 weeks. The first hemiface treated in the Main trial was consequently observed throughout the Extension trial, allowing for a further 12‐week assessment of outcomes (total 24 weeks). In light of an additional 12 weeks of treatment on the contralateral face, the patient compliance rate was excellent, with 91.9% of the total number of patients receiving at least 80% of the treatments. Patients with a baseline IGA grade of 2 (mild) on the treated hemiface demonstrated a success rate of 58.3 and 66.7% at weeks 6 and 12, respectively. At these same time points, subjects with a baseline IGA grade of 3 (moderate) demonstrated a success rate of 81.8 and 90.0%. Patients with a baseline IGA grade of 4 (severe) demonstrated a success rate of 100% at both week 6 and week 12. When evaluating the originally treated hemifaces from the Main trial, the rate of return to baseline at 24 weeks was calculated to be 15.5%. This latter outcome confirmed the long duration of effect following treatment. The patient safety profile was also excellent, with very few related adverse events. The BioPhotonic System, which is comprised of LED blue light phototherapy and photo‐converter chromophores, provides long‐term efficacy and safety in the treatment of acne vulgaris, with a rate of compliance above what is generally observed in a young population of patients suffering from acne vulgaris, especially in light of sequential enrollment in a study treating one hemiface.